A new and remarkable aquatic species of Schismatoglottis (Araceae) from the Philippines - Boyce, P.C; Medecilo, Melanie P.; Wong, Sin Yeng (BGBM Berlin-Dahlem., 2015)
Schismatoglottis prietoi P. C. Boyce, Medecilo & S. Y. Wong (Araceae: Schismatoglottideae), the first recorded aquatic species of Schismatoglottis Zoll. & Moritzi, is described and illustrated from Cebu and Luzon islands in the Philippines.